Hidden from the wind and enjoying the water (藏风得水): the traditional cosmology of fengshui and the shaping of Dong villages in Southwestern China. (4th July 2019) - Li, Xuemei; Li, Weiye; Smith, Kendra S.; Smith, Albert C.
Abstract: When organising their villages, the Dong interpret the natural environment from a culture-based perspective within their traditional cosmology. This paper explores the metaphorical meanings of the winds, the water of life and the awareness of life breath qi as they are integrated into the practice of fengshui . These principles are applied by the Dong people when organising their villages, monuments and vernacular architecture. This paper particularly examines several Dong communities that share similar topography but were developed in strikingly different ways. In conclusion, this paper argues that the approach of the Dong, when siting their villages, is based on their traditional cosmology and the context of local culture but also their interpretation responding to specific situations that produce different solutions.